Chemical compositions of two endemic Thymus species essential oil - Samira Jaberi; Mahmoodreza Moein; Jafari Azizolah; Forough Karami (Shiraz University of Medical Sciences, 2015)
Thymus is one of the most important members of Lamiaceae family. Aerial parts of the plant have been widely used in medicine. It has been reported that most of these effects are related to phenolic compounds especially thymol and carvacrol in Thymus essential oil.In this study, aerial parts of Thymus daenensis and Thymus lancifolius were collected from Kohgiluyeh and Boyer-Ahmad. Essential oil of aerial parts of these plants was gained by hydrodistillation method and the chemical compositions were analyzed by gas chromatography/ Mass spectrometry (GC/MS). The major components of the essential oil of Thymus daenensis were thymol (39.91%), carvacrol (29.93%), linalool (5.55%), caryophyllene (3.5%) and geraniol (3.09%), whereas the major components of the essential oil of Thymus lancifolius were: carvacrol (25.55%), thymol (20.79%), linalool (16.8%), α- terpineol(6.34%), borneol (4.00%), caryophyllene (3.98%), p-cymene (3.38%) and cis-linalool oxide (3.21%). Linalool was reported as another major component in Thymus lancifolius.